Red Blood Cell Response to Blast Levels of Force Impartations Into Freely Moveable Fluid Surfaces Inside a Closed Container - Smith, David; Franco, Robert; DiCesare, Christopher A.; Schneider, Daniel K.; McGill, Chuck; Smith, Quinton D.; Myer, Gregory D. (Frontiers in Physics, 2018)
Background: Blast waves have plagued mankind for centuries, yet their interaction with blood has been largely overlooked. Recent studies of ways to mitigate traumatic brain injury (TBI) in sport have utilized slosh reducing techniques with varying success. However, hydrodynamic principles have not been used to assess the interaction of intense blast waves and the red blood cells themselves. Objective: To establish the benefits of slosh reduction by analyzing the degree of damaging effects from a blast wave imparted on human red blood cells both fully and partially contained by rigid surfaces. Methods: Approximately 40 mL of blood was collected from 13 males and 25 females ages 18 – 55 and aliquoted into three separate steel containers (5 cc- control, 15 cc- full and 10 cc -partially filled) in preparation for blast testing. An improvised explosive device (IED) blast level model (Vandenberg) was developed by using a nail gun plunger to impart approximately 150 kPa of pressure over a 4 to 6 microsecond timespan into a target container. Blood in steel containers, with and without IED blast exposure, was assayed for cell hemolysis products including serum free hemoglobin (HgB), lactate dehydrogenase (LDH), and potassium (K-ABL) when the containers were fully-filled or partially filled (no-slosh versus slosh). Hemolysis products were measured 1 hour, 4 hrs, 24 hrs, 48 hrs, and 72 hrs after blast exposure. Results: In both the slosh and no-slosh groups, hemolysis increased significantly at each time point after IED blast energy impartation. However, the no-slosh blood samples had less hemolysis. Compared to the slosh group, blood from the no slosh group contained less extracellular HgB (p<.0001), lactate dehydrogenase (LDH) (p<.0001), and potassium (K+) (p<.0001) at all time points. Conclusions: Damage to human blood resulting from the impartation of a force similar to an IED blast was mitigated by fully containing blood within a volume and thereby reducing fluid slosh.